Work and Industrial Relations: Towards a New Agenda - Lansbury, Russell (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2009)
The relevance and continuing existence of industrial relations, as a field of academic study, is facing a number of challenges, particularly in English-speaking countries, as union membership declines, collective bargaining coverage shrinks and the number of strikes wanes each year. Yet issues of employment and workplace relations remain significant to economic prosperity and social harmony, particularly with the changing nature of work and of employment contracts. Furthermore, there are a number of other means by which employee voice is heard, through the agency of non-government organizations, community groups and various consultative bodies. In order to reinforce its relevance, industrial relations needs to include new actors, cover a wider range of issues and adopt a multi-level approach which incorporates both local and global dimensions.